Effect of CYP Inducers/Inhibitors on Topiramate Concentration: Clinical Value of Therapeutic Drug Monitoring. Issue 1 (February 2017) - Yamamoto, Yoshiaki; Takahashi, Yukitoshi; Imai, Katsumi; Kagawa, Yoshiyuki; Inoue, Yushi
Abstract : Background: This study investigated the pharmacokinetic interactions between topiramate (TPM) and concomitant antiepileptic drugs and evaluated the therapeutic concentration range of TPM and the effect of the achieved plasma concentration on the retention rate of TPM therapy. Methods: A total of 1217 plasma samples obtained from 610 patients were retrospectively investigated, and the concentration-to-dose ratio (CD ratio) of TPM was compared among patients on various antiepileptic drug regimens. In addition, the therapeutic concentration of TPM was reviewed in patients on long-term therapy, and factors influencing the retention rate of TPM were analyzed by the Kaplan–Meier method. Results: Among patients using hepatic enzyme inducers (phenytoin, phenobarbital, and carbamazepine), the CD ratio was reduced by 45.4% in adults and 33.3% in children. Patients taking phenytoin concomitantly had a significantly lower CD ratio than patients taking phenobarbital or carbamazepine. Among noninducers, concomitant use of stiripentol increased the CD ratio. In 276 patients who remained on TPM therapy for more than 2 years, the mean therapeutic concentration was 5.1 mcg/mL (15.0 μmol/L). The estimated retention day was significantly higher for patients with a TPM concentration >5 mcg/mL than that for patients with a concentration <5 mcg/mL (945 versus 802 days; P = 0.007 by the log-rank test). Also, patients without hepatic enzyme inducers had a significantly higher retention rate than patients using such inducers ( P = 0.002). Conclusions: Concomitant use of hepatic enzyme inducers markedly reduced the plasma TPM concentration and can decrease its antiepileptic effect. A therapeutic concentration of >5 mcg/mL TPM was significantly associated with continuation of therapy, and therapeutic drug monitoring can be helpful.